Pengaruh Penambahan Mobilisasi Saraf Terhadap Penurunan Nyeri Ischialgia Oleh Karena Hernia Nucleus Pulposus Di RS St Elisabeth Semarang - Rikardasari, Irine; , Dwi Rosella Komala Sari S.Fis, M.Fis; , Totok Budi Santoso , S.Fis , MPH (2015)
Ischialgia is one manisfestation of lower back pain because the nerve entrapment ischiadicus. Ishialgia is pain that radiates along the nerve roots trip (hypotesia, parastesia atau disastesia) ishiadicus. Objective : Research purposed to determine the effect of neural mobilization against decrease in pain of hernia nucleus pulposus in St. Elizabeth Hospital Semarang. This research was done in St. Elizabeth Hospital Semarang at 10 April until 30 May 2015. Method : This research used Quasi Experimental Design with pre test and post test design.The research population of this research was 16 people with 16 people as the sample taken according to inclution dan exclution. Statistical test done by non parametric test. Measuremnet Instrument : Quadruple Analogue Scale. Result : test hypothesis with wilcoxon test in group I (TENS) obtain p = 0,012 and on group II (TENS and nerve mobilization) obatained p = 0,012. Hypothesis test intergroup after treatment with mann whitney test obtained p = 0,752. Conclution : TENS and nerve mobilization are no better than TENS to decrease in pain.